A comparison of psychosocial and psychiatric features of mentally capable versus mentally incapable individuals referred by the courts for forensic psychiatric observation in relation to an alleged sexual offence - Roos, Johannes Louw (University of Pretoria, 2018)
Thesis (PhD)- University of Pretoria, 2018.